THE EFFECT OF ADDITIONAL CONCENTRATE PROTEIN FROM DIFFERENT FISH TYPES OF CONSUMER RECEIPT IN FRESH BREAD - Hendri Mustari Saputra; Dewita Dewita; Sumarto Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This research was to determine the effect of the addition protein concentrates from different types of catfish (P. hypopthalmus, C. gariepinus and P. albilabris) to consumer acceptance of bread. The method used is an experiment using non-factorial completely randomized design (RAL), with 4 levels of treatment namely K0 (control), K1 (addition of  Shark Catfish  KPI), K2 (addition of Walking Catfish KPI), K3 (addition of Eel Tailed Catfish KPI) respectively 50 g. The parameters measured in this study are organoleptic test and proximate analysis including water, ash, protein and fat content. The results showed that the addition of KPI 50 g was the best in K1, with an organoleptic appearence (3.38) with characteristics yellow and there were red spots on the surface of fresh bread, flavor (3.47) with the characteristic taste of plain bread and the fish feels a little, aroma (3.31) with the characteristic aroma of fresh bread and a little fish smell and texture (3.32) with the characteristics of a soft and elastic texture. Based on proximate analysis, plain bread with the addition ofShark Catfish  KPI has a water content of 33.86%, ash content of 0.66%, protein content of 16.30% and fat content of 4.56%.Keywords :C. gariepinus,Fish protein concentrate, Fresh bread, P. hypopthalmus, P. albilabris